L'abus de pouvoir des représentants légaux dans le droit familial du Québec - Brière, Germain (Les Cahiers de droit, 1978)
In order to determine the nature of the abuse of power of the legal representatives in Quebec family law, one must identify the different cases of legal representation and study the powers of the different representatives. Tutorship is the mechanism for the protection of the non emancipated minor. As a rule, the tutor represents his pupil in civil acts; but in some cases he has no power to act, in other cases he must get the judge's authorization, while in a third category of cases he must comply with special formalities. Consequently, there can be absence of power, misappropriation of power, bad utilization of power or dereliction of duty. Curatorship is used for different kinds of interdicted persons. The powers and liabilities of the curator to an interdicted person are generally the same as those of the tutor. The legal mandate of the married woman is the power to represent her husband for the current needs of the household and the maintenance of the children. In this case, the abuse mainly takes the form of an excess of power. The effects of the abuse of power must primarily be considered in the relations between the represented person and his legal representative; we must ask ourselves if the legal representative is liable for damages, if his acts can be annulled and if there can be withdrawal from office. There are also effects to be considered in the relationship between the legal representative and the third persons, as well as in the relationship between the represented person and the third parties.